Cambodia, 1975-1978 : Rendezvous with Death - Jackson, Karl D. (Book collections on Project MUSE., 1989)
A collection of essays, which search for what can be explained in the ultimately inexplicable evils perpetrated by the Khmer Rouge. It is accompanied by a photo essay that provides visual evidence of the tragedy of Cambodia's autogenocide.